Central Airway Obstruction: Diagnostic Challenges and Management Strategies in Subglottic Stenosis and Poly Chondrites with Case Studies - Bulbulia, Bashir Ahmed; Ahmed, M R (British Journal of Healthcare and Medical Research, 2025)
Tumours or strictures compressing the trachea /bronchial tree cause central airway obstruction (CAO). Subglottic stenosis are a cause of respiratory symptoms and distress. Idiopathic sub glottic stenosis (ISGS) is a rare disease occurring mainly in women and has a history of recurrences. Endoscopic laser microsurgery and balloon dilatation are used in the management of strictures. Recurring strictures may require tracheoplasty. Poly chondrites is a rare disorder causing poly arthritis and inflammation of cartilaginous tissue. Inflammatory changes in the lung cause tracheobronchomalacia (TBM) and lung collapse. Relapsing polychondritis (RP) effecting the airway is life threatening as there is dynamic airway closure during expiration. The medical therapy in RP includes steroids, disease modifying agents ( methotrexate) and biologics. Surgical interventions include tracheostomies and tracheobronchial stents for severe forms of the illness.